Effect of glutathione on the quality of frozen buck semen - HAZARIKA, S B; BHUYAN, D; DEKA, B C; SINHA, S; BISWAS, R K; DUTTA, D J; DAS, A; BORAH, P; DEWRY, R K (The Indian Journal of Animal Sciences, 2016)
Ejaculates (30) collected twice weekly from five Beetal bucks were used to study the effect of addition of 0 (control), 4 mM, 6 mM and 8 mM glutathione on the quality of frozen Beetal buck semen by split sample technique. After removal of seminal plasma, the semen was primarily extended with Tris extender (1: 5) considering the volume of semen prior to removal of seminal plasma and then split into 4 parts and finally extended with equal volume of Tris extender that rose the extension rate to 1: 10. The mean percentage of sperm motility, live sperm, live intact acrosome, HOST-reacted sperm was significantly higher in Tris extender containing 4 mM glutathione than that containing 6 mM, 8 mM glutathione and control. The release of ALT and AST from post-thaw spermatozoa was also the lowest in semen containing 4mM concentration of glutathione. Based on post-thaw sperm motility, live sperm, live intact acrosome, HOST-reacted sperm, and ALT and AST release, addition of 4 mM glutathione in Tris extender was superior to 6 mM, 8 mM and 0 mM (control). It was concluded that glutathione at 4 mM could be used as an antioxidant in Tris for cryopreservation of Beetal buck semen which could provide a better environment in protecting the functional capacity of spermatozoa.